Pigmentos nanométricos de alumina dopada com ferro, níquel e manganês - Lima, Renata Cristina de (2006)
In the recent years, the necessity of ceramic pigments production with new shades and variable distributions of particle size has increased considerably. The color and size of pigment particles are responsible for important applications in the ceramic industries, resins, cosmetics, dyes, plastics and dentistry materials. In this work, nanometric pigments based on iron, nickel and manganese doped Al2O3 (1, 2, 4 and 8 mol% of cations) were prepared using the polymeric precursor method. The powders were calcinated in temperatures ranging from 700 to 1100°C. The γ-Al2O3 and α-Al2O3 crystalline phases obtained at 900 and 1100°C, respectively, were identified by X-ray diffraction. Using the Rietveld Method was possible to quantify the α-Al2O3 solid solution containing Fe3+, Ni2+ and Mn2+. The secondary phases, NiAl2O4 and Mn3O4, increased with the doping concentration of the cations Ni2+ and Mn2+, respectively. Infrared spectroscopy allowed the characterization of the alumina vibrational modes and identification the octahedral and tetrahedral sites of the Al2O3 structure. Nanometric particles, around 10 nm, of iron, nickel and manganese doped Al2O3 obtained at 900°C were observed by transmission electronic microscopy images. The electronic transitions of Fe3+, Ni2+ and Mn2+ were characterized by ultraviolet-visible reflectance spectroscopy. The pigment colors, yellow for iron, blue and green for nickel, and brown and red for manganese were described by Colorimetric analyses using the CIELab colors system. These colors are related with the amount of chromophores in the alumina composition, the powders calcination temperature and the ions occupation sites in the alumina lattice. The obtained nanometric pigments have potential applications in cosmetic and polymers areas.